HPLC-UV/VIS for Determination of Ipratropium Bromide Mixed with Salbuterol, Beclomethasone Propionate and Budesonide using Dual Wavelength-Detection Method - Haihua, Guo; Rui, Zhang; Liangjun, Deng; Meng, Li; Sha, Li; Suqing, Zhao (Drug Research, 2023)
Background Inhalation preparation involves liquid or solid raw materials for delivering to lungs as aerosol or vapor. The liquid preparation for nebulizer is effective for convenient use and patient compliance and it has been extensively used in the treatment of clinical lung diseases. Clinical staff often mixes the compound ipratropium bromide with beclomethasone propionate and budesonide inhaler but reference values of inhalants for clinical use need to be established for simplifying the operation procedure. The high-performance liquid chromatography (HPLC) method of compound ipratropium bromide solution, beclomethasone propionate suspension and budesonide suspension after mixed atomization was studied.Methods The specificity, linearity, recovery (accuracy), precision and stability of compound ipratropium bromide, beclomethasone propionate and budesonide were tested to verify the developed liquid phase method.Results The developed liquid phase method had high specificity, linear R2≥0,999, recovery (accuracy) RSD (relative standard deviation) less than 2%, precision RSD less than 2,0%, and stability RSD less than 2,0%.Conclusion The liquid phase methodology developed in this study can be used for the determination of compound ipratropium bromide mixed with beclomethasone propionate and budesonide. The current methodology can also be used to provide a reference for the determination of its content after mixing, and further data support for its clinical medication.
Keywords: salbuterol; ipratropium bromide; beclomethasone propionate; budesonide; detection of mixture utilization; dual wavelength-detection for HPLC method